Tuna in the International market for seafood - Paquotte P. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
Tuna is one of the major products in seafood international trade. World tuna landings are around 3.5 million tons per year. All tuna fishing countries are involved in international trade. One third of the tuna production is exported as fresh, chilled or frozen fish. The main final markets for tuna are in USA, Japan and the European Union, like for most seafood products. The tuna industry is more and more concentrated, with a very limited number of actors at the marketing level. While the market for canned tuna is stabilized in Europe and recessing in the US, the market for fresh or frozen tuna has good perspectives of development.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)